Oral adverse effects of head and neck radiotherapy: literature review and suggestion of a clinical oral care guideline for irradiated patients - Elen de Souza Tolentino; Bruna Stuchi Centurion; Lúcia Helena Caetano Ferreira; Andréia Pereira de Souza; José Humberto Damante; Izabel Regina Fischer Rubira-Bullen (University of São Paulo, 2011)
Radiotherapy, alone or associated with surgery or chemotherapy, produces a significant increase in cure rates for many malignancies of the head and neck region. However, high doses of radiation in large areas, including the oral mucosa, may result in several undesired reactions that manifest during or after the completion of therapy. The multidisciplinary management is the best alternative to minimize or even prevent such reactions, and the dentist has a fundamental role in this context. This paper reviews the literature related to the main oral sequelae from head and neck radiotherapy and establishes clinical oral management protocol for these irradiated patients.